A temporal examination of elite performers sources of sport-confidence - Kingston, K.; Lane, A.; Thomas, O. (The Sport Psychologist, 2010)
This study examined temporal changes in sources of sport-confidence during the build up to an important competition. Elite individual athletes (N = 54) completed the Sources of Sport-Confidence Questionnaire (SSCQ) at five precompetition phases (6 weeks, 4 weeks, 3 weeks, 2 weeks and 1 week before competition). A two-factor (gender x time-to-competition) MANOVA revealed no significant interactions, but highlighted both time-to-competition and gender main effects. Time-to-competition main effects indicated the importance placed upon demonstration of ability, physical/mental preparation, physical self-presentation and situational favorableness sources of sport-confidence changed during the precompetition phase. Gender main effects revealed that female athletes demonstrated a significantly greater reliance on sources associated with mastery, physical self-presentation, social support, environmental comfort and coach`s leadership than male athletes. These findings emphasize the benefit of considering sources of sport-confidence as competition approaches; they may have implications for the design and timing of confidence based interventions.